Peran Kredit Usaha Rakyat Syariah Dalam Meningkatkan Kesejahteraan Usaha Budidaya Perikanan Fansuri Farm (Anggota Kelompok Ikan Sadar Jati Mulyo) - Silvi Yurike Farera; Meirini, Dianita (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2023)
Sharia People's Business Credit is a regulatory program from the government specifically aimed at Micro, Small and Medium Enterprises as a source of capital. This study aims to determine the welfare of the Fansuri Farm aquaculture business on the use of Sharia People's Business Credit in terms of indicators of income level, expenditure level, education level, health level, living conditions and facilities. This research method is qualitative, with the type of case study research. Data collection techniques using interview and observation methods. The results of the study can be concluded that Fansuri Farm feels a significant impact on the use of Sharia People's Business Credit financing where increased welfare and business development can be seen from the increase in the number of ponds and fish capacity. The advantage of Fansuri Farm fish farming is that it already has a wide market share, while the obstacles are declining fish prices and slowly rising fish feed prices.